Grenade - Gratz, Alan, 1972- (Scholastic Press, 2018)
On April 1, 1945 with the battle of Okinawa beginning, fourteen-year-old native Okinawan Hideki, drafted into the Blood and Iron Student Corps, is handed two grenades and told to go kill American soldiers; small for his age Hideki does not really want to kill anyone, he just wants to find his family, and his struggle across the island will finally bring him face-to-face with Ray, a marine in his very first battle--and the choice he makes then will change his life forever.